Fuelbreak effectiveness against wind-driven and plume-dominated fires: A 3D numerical study. (September 2021) - Frangieh, Nicolas; Accary, Gilbert; Rossi, Jean-Louis; Morvan, Dominique; Meradji, Sofiane; Marcelli, Thierry; Chatelon, François-Joseph
Abstract: The effectiveness of a fuelbreak, created in a homogeneous grassland on a flat terrain, was studied numerically. The analysis relies on 3D numerical simulations that were performed using a detailed physical-fire-model (FIRESTAR3D) based on a multiphase formulation. To avoid border effects, calculations were carried out by imposing periodic boundary conditions along the two lateral sides of the computational domain, reproducing that way a quasi-infinitely long fire front. A total of 72 simulations were carried out for various wind speeds, fuel heights, and fuelbreak widths, which allowed to cover a large spectrum of fire behaviour, ranging from plume-dominated fires to wind-driven fires. The results were classified in three main categories: 1- "Propagation" if fire crossed the fuelbreak with a continuous fire front, 2- "Overshooting" and "Marginal" if fire marginally crosses the fuelbreak with the formation of burning pockets, and 3- "No propagation" if fire does not cross at all the fuelbreak. The ratio of fuelbreak width to fuel height, marking the "Propagation"/"No propagation" transition, was found to be scaled with Byram's convection number N c as 75.07 ×  N c −0.46 . The numerical results were also compared to an operational wildfire engineering tool (DIMZAL) dedicated to fuelbreaks dimensioning. Highlights: Fuel break effectiveness was investigated numerically. Classification: Propagation, Overshooting, Marginal, No Propagation.